Recent advances on kinetics of carbon dioxide capture using solid sorbents at elevated temperatures. (1st June 2020) - Ji, Guozhao; Yang, Hang; Memon, Muhammad Zaki; Gao, Yuan; Qu, Boyu; Fu, Weng; Olguin, Gianni; Zhao, Ming; Li, Aimin
Highlights: The importance of CO2 sorption kinetics and effective capacity were highlighted. CO2 capture in Ca-based sorbents generally follow diffusion-limited model. Molten carrier could improve the CO2 capture kinetics in Mg-based sorbents. Expanding interlayer spacing via anion exchange could improve CO2 sorption in LDH. Alkali ceramic sorbents capture CO2 via nucleation and nuclei growth mechanism. Abstract: Developing carbon capture and storage (CCS) technology is a promising route to tackle the rising level of atmospheric carbon dioxide (CO2 ). Capturing CO2 at high temperature by solid sorbents is attractive in both pre-combustion and post-combustion scenarios. This paper highlights the importance of CO2 sorption kinetics and reviews the published research available on the calcium-based sorbents, magnesium-based sorbents, layered double hydroxide sorbents and alkali ceramic-based sorbents. Insights are provided into the main factors affecting the CO2 sorption kinetics such as reaction and mass transfer mechanism, material microstructures and reaction operating conditions. Finally, a few possible research gaps are identified and recommendations for future research are proposed.